Tipos de condução de hastes na produção e na qualidade de mini tomate em manejo orgânico - Candian, Joara Secchi [UNESP] (2015)
Tomato is an important vegetable crop product, being highly valued by consumers of organic food. Features such as production, size and taste of the fruits can be greatly influenced by plant density that can be increased by reducing the spacing or by increasing the number of stem in each plant. The experiment was conducted in São Manuel-SP between the months of August 2013 on January 2014, with the objective of evaluating the influence of the number of stems per plant and the conduction type in production and physicochemical characteristics of fruits of hybrid Coco tomato, type mini tomatoes. The experiment was conducted in protected cultivation under organic management. The treatments consisted of four different ways of conduction: 2 traditional stems (main stem and stem below the 1st inflorescence); 2 stems coming from axillary buds of cotyledon leaves (named as bottom stem conduction), due to pruning the apical meristem of the plant just above the cotyledons with the seeldlings still in the tray; 3 stems (main stem and two stems side below the 1st and 2nd inflorescences) and 4 stems coming from bottom stem. The fruits were harvested when they wer totally red. It was evaluated total number of fruits per plant, production (g plant -1), earliness production (adding the first four crops) and physico-chemical characteristics (average weight and fruit diameter, pH, titratable acidity, soluble solids, ratio, reducing sugars, ascorbic acid, lycopene, β -carotene, chlorophyll a and b and mass loss (%)) of the fruit. The number and the conduct of the stems did not affect the production of fruits per plant (g plant-1), but with the increase ...